Hypotrichosis and juvenile macular dystrophy caused by CDH3 mutation: A candidate disease for retinal gene therapy - Singh, Mandeep S. (Sci Rep, 2016)
Hypotrichosis with juvenile macular dystrophy (HJMD) is an autosomal recessive disorder that causes childhood visual impairment. HJMD is caused by mutations in CDH3 which encodes cadherin-3, a protein expressed in retinal pigment epithelium (RPE) cells that may have a key role in intercellular adhesion. We present a case of HJMD and analyse its phenotypic and molecular characteristics to assess the potential for retinal gene therapy as a means of preventing severe visual loss in this condition. Longitudinal in vivo imaging of the retina showed the relative anatomical preservation of the macula, which suggested the presence of a therapeutic window for gene augmentation therapy to preserve visual acuity. The coding sequence of CDH3 fits within the packaging limit of recombinant adeno-associated virus vectors that have been shown to be safe in clinical trials and can efficiently target RPE cells. This report expands the number of reported cases of HJMD and highlights the phenotypic characteristics to consider when selecting candidates for retinal gene therapy.